Blockchain Technology in Advertising Campaigns - A. A. Efremov; K. S. Gerashchenko; M. N. Salapura (Цифровая трансформация)
The article is devoted to the peculiarities of blockchain technology in terms of its application in the economy. The emphasis is on the impact of this technology on the advertising market. In the course of the study, the main features and tasks of blockchain systems were identified, as well as the actions of large companies on their implementation were analyzed. The consider the relevance of the research object, which is dictated by the ever-increasing role of cryptocurrency assets and processes in the modern world. The blockchain technology is studied, the economic justification of its introduction into the ongoing advertising campaigns as a means of improving the information communication process is given. The features of the functioning of systems related to cryptocurrencies, as well as the pros and cons of decentralized data storage technology are analyzed. The main problems that arise when using blockchain technology are described and ways to solve them are proposed. The definitions of a number of categories of the subject area have been clarified. Recommendations are given for the effective functioning of advertising campaigns in the field of digital marketing.